Reconstruction of the Concept of Justice in Economic Analysis of Law: A Sharia Economic Perspective: Rekonstruksi Konsep Keadilan dalam Economic Analysis of Law :Perspektif Ekonomi Syariah - Sodiman, Sodiman; Akbar, Muhamad (Robust: Research of Business and Economics Studies, 2026)
This study aims to analyze and reconstruct the concept of justice in the Economic Analysis of Law (EAL) based on the perspective of sharia economics. This study is motivated by criticism of the conventional EAL paradigm that places economic efficiency, market rationality, and utility maximization as the main measures of legal effectiveness. This approach is considered not to be able to realize substantive justice because it does not pay attention to the distribution of welfare, social protection, and moral values in economic activities. The research uses a qualitative method with a library research approach, and is supported by conceptual and philosophical approaches. Data were obtained from various relevant scientific literature, then analyzed using content analysis and descriptive-critical analysis. The results of the study show that justice in the sharia economy is multidimensional because it includes economic efficiency, equitable distribution of welfare, protection of vulnerable groups, human development, social responsibility, and environmental sustainability. The findings of the study confirm that maqāṣid al-sharī'ah is the main foundation in building the concept of economic law justice through the principles of benefit, social balance, and distributive justice. Based on these findings, this study offers the Sharia Economic Analysis of Law paradigm as an alternative approach that places maqāṣid al-sharī'ah as a normative basis in assessing the effectiveness of economic law to realize sustainable welfare and social justice.